Molar pregnancy: A fifteen - year experience of a single tertiary institution - Camroodien, Sedick (Department of Obstetrics and Gynaecology, 2023)
Background: Gestational trophoblastic disease (GTD) is a group of uncommon conditions associated with pregnancy that arise from abnormal placental trophoblastic tissue following abnormal fertilization (1). Despite its rarity, it is of clinical and epidemiological importance because it affects women in the reproductive age group and is associated with morbidities and may sometimes be fatal (2). Molar pregnancy represents as two entities, complete or partial mole, which are mostly benign and can be distinguished by gross morphology, histopathology and genetic analysis (3). The incidence and etiologic factors contributing to the development of GTD have been difficult to characterize. Problems in accumulating reliable epidemiologic data can be attributed to inconsistencies in case definitions, inability to adequately characterize the population at risk, no centralized databases, lack of well-chosen control groups against which to compare possible risk factors, and rarity of the diseases (4). Several potential risk factors for molar pregnancies have been suggested. These include paternal age, vitamin deficiencies, maternal genetic translocations and environmental toxins. The only clear data relate to the impact of maternal age and the previous occurrence of a prior molar pregnancy (3,5,6). With minimal data from African countries about GTD, there remains a greater need for early recognition, timely referral and prompt and proper treatment of this condition (7). Aim: The aim of this descriptive study was to provide a detailed analysis of all patients diagnosed with molar pregnancy at Groote Schuur hospital (GSH) for the period January 2004 – December 2019. Methodology: This was a retrospective descriptive study of all women who were referred and followed up at the molar clinic at GSH with a confirmed histological diagnosis of molar pregnancy during the period 2004 – 2019. Subjects were identified from the molar clinic register at GSH, and folders retrieved for those meeting the inclusion criteria. Analysis was by simple frequencies and rates using SSPS statistical software. Subgroup analyses was performed by chi squared and t-tests. Results: There were 554 057 deliveries and 235 cases of molar pregnancies during that period, with an incidence of 0.42/1000 deliveries. Women aged 20 – 40 years and multiparous women constituted 78.7% and 59.8% of patients. Most (51.3%) patients were diagnosed in their second trimester. The most common presenting complaint was vaginal bleeding (37.4%), and the commonest complication was hyperthyroidism (16.6%). Twenty-six (11.2%) patients required a blood transfusion. Ten patients (4.2%) required a second evacuation with only 4 patients (1.7%) requiring a hysterectomy due to excessive haemorrhage. Patients with molar pregnancy normalized their HCG at 12 weeks post evacuation. There were 47 cases of persistent disease, of which 42 cases were referred for chemotherapy. The remaining 5 cases did not require chemotherapy as they achieved spontaneous regression after the second evacuation. Suction evacuation was performed in 97.4%. With regards to follow up, 44.3% of patients defaulted post evacuation surveillance and care. Conclusion: As the incidence of molar pregnancy in our centre continues to decline, it is important that we take the necessary steps to improve the follow-up protocols for patients with this condition. Doing so will avoid experiencing loss to follow-up.